CSR and Human Rights: Normative Review of Corporate Obligations in Workers' - Wardah, Siti Syarifah Wafiqah (Universitas Negeri Makassar, 2025)
Corporate Social Responsibility (CSR) has an important role in protecting human rights, especially workers' rights, by encouraging companies to adopt ethical and responsible practices. This research aims to examine the obligations of corporations in protecting workers' rights through the implementation of CSR. The method used is a literature study and analysis of policy documents related to CSR and workers' rights. The results show that CSR can improve workers' welfare through the protection of basic rights, such as decent wages, a safe working environment, and the right to organize. However, CSR implementation faces challenges, including a lack of management understanding, limited resources, and a lack of transparency and accountability. In addition, existing regulations often lack clarity in their application, hindering the effectiveness of CSR policies. Therefore, collaboration between the government, companies, and other stakeholders is needed to enhance more transparent and sustainable CSR implementation to ensure the protection of workers' rights. Keywords: Corporate Social Responsibility, Workers' Rights, Social Responsibility, Regulation, Workers' Welfare.